Sport supplement use in Brazilian cyclists: Where is the information coming from? - Perim, P.; Mazzolani, B.; Farias de Oliveira, L.; Symon, K.; Dolan, E.; Saunders, B. (Journal of Science and Cycling, 2019)
Background: Prevalence of dietary supplement use by athletes has been widely investigated, with prevalence in Brazil ranging from 37% to 98% (Nabuco et al., 2016). The American College of Sports Medicine categorises supplements as sports foods, medical supplements, specific performance supplements and others (Thomas et al., 2016). However, not all supplements are supported by strong scientific evidence according to the International Olympic Committee (Maughan et al., 2018). Commonly employed sports and functional foods with solid evidence include sports/energy drinks and gels, protein supplements and sports bars while only five supplements have good to strong evidence of achieving benefits to performance when used in specific scenarios (beta-alanine, caffeine, sodium bicarbonate, nitrate and creatine). Nowadays, there is an overwhelming amount of information readily available, albeit not all from reputable scientific sources, making it difficult for individuals to make the right choices. The dietary supplement market promotes countless supplements despite growing evidence that does not support their use, such as HM-ß (Valenzuela et al., 2019), glutamine (Ramezani Ahmadi et al., 2018) and BCAAs (Wolfe, 2017). It is of the utmost importance that individuals procure reliable information to guide their supplementation choices. The main aim of this study was to investigate supplementation use, and sources of supplement information in Brazilian cyclists.